(untitled) (The Peerian Journal, 2026)
This article analyzes effective methods for the formation of acmeological approaches in students. In modern educational conditions, the self-development of the individual and achieving professional perfection are of great importance. The study examines pedagogical approaches and mechanisms aimed at the full realization of the personal and professional potential of students. The article highlights interactive methods and innovative technologies that serve the development of acmeological competencies. The results help to form self-awareness, goal-setting and continuous improvement skills in students.